Operando observation of the Taylor cone during electrospinning by multiple synchrotron X-ray techniques - Sui, T; Ying, S; Titov, K; Dolbnya, I; Tan, J; Korsunsky, A (Elsevier, 2016)
Electrospinning has introduced a powerful means of fabricating polymer nanofibres into the broader realm of nanotechnology and polymer science. It has attracted considerable attention due to its outstanding versatility and numerous applications, such as the incorporation of nanoparticles within the fibres. The Taylor cone formed at the tip of the syringe that delivers the solution (or melt) plays an important role in controlling the structure, and thus the mechanical and functional properties of the fibres produced. Characterising the dynamic processes that occur within the cone is a challenging experimental task. In this study, operando synchrotron X-ray techniques were used to observe the Taylor cone formed during electrospinning. The combination of imaging with spatially resolved mapping by small angle and wide angle X-ray scattering provides a wealth of information about the cone exterior shape, surface orientation and inner morphology. This express note illustrates the rich body of data that can be collected using multi-modal X-ray imaging and scattering setup. From the observed patterns it is possible to extract information concerning particle density and flow patterns that persist within the Taylor cone.